Respuesta :

Answers and justitication:

1) (7x)^3 + 8→ 8 added to the cube of 7x

becasue the cube of 7x is (7x)^3 and then 8 is added to it.

2) (7x + 8)^3 → the cube of the sum of 7x + 8

because first you add 8 to 7x and then the result is cubed.

3) 7x^3 + 8 → 8 added to 7 and x cubed.

4) 7(x+8)^3 → 7 times the cube of the sum of x and 8.

because first 8 is added to 8, then the result is cubed, and finally the result is multiplied by 7.
The verbal description are matched with the mathematical expressions as follows:


The cube of the sum of 7x and 8 ⇒ (7x + 8)³

8 added to 7 and x cubed ⇒ 7x³ + 8

8 added to the cube of 7x ⇒ (7x)³ + 8

7 times the cube of the sum of x and 8 ⇒ 7(x + 8)³
ACCESS MORE